Transglycosylation Properties of a Novel α-1, 4-Glucanotransferase from Bacteroides thetaiotaomicron and Its Application in Developing an α-Glucosidase-Specific Inhibitor. (17th December 2018) - Choi, Hye-Jeong; Ko, Dam-Seul; Kim, Na-Ri; Choung, Woo-Jae; Koo, Ye-Seul; Jeong, Da-Woon; Shim, Jae-Hoon
Abstract : In this study, α -glucanotransferase from Bacteroides thetaiotaomicron was expressed in Escherichia coli and characterized. Conserved amino-acid sequence alignment showed that Bacteroides thetaiotaomicron α -glucanotransferase (Bt α GTase) belongs to the glycoside hydrolase family 77. The enzyme exhibited optimal catalytic activity at 60°C and pH 3.0. Bt α GTase catalyzed transglycosylation reactions that produced only glycosyl or maltosyl transfer products, which are preferable for the generation of transglycosylated products with high yield. The 1-deoxynojirimycin (DNJ) glycosylation product G1-DNJ was generated using Bt α GTase, and the inhibitory effect of G1-DNJ was analyzed. A kinetic study of inhibition revealed that G1-DNJ inhibited α -glucosidase to a greater extent than did DNJ but did not show any inhibitory effects towards α -amylase, suggesting that G1-DNJ is a potential candidate for the prevention of diabetes.